Domain-specific physical literacy profiles of elementary physical education teachers in rhythmic activity instruction - Ranintya Meikahani; Aris Fajar Pambudi; Soni Nopembri; Hari Yuliarto; Nur Sita Utami (Lentera Negeri, 2026)
Teachers' own physical literacy, a necessary condition for effective instruction, remains relatively unexplored, especially in the context of rhythmic activity within non-Western elementary school settings. This paper investigates the level of physical literacy of teachers involved in rhythm-based physical education activities across five domains: cognitive understanding, motor competence, balance ability, object control, and environmental participation. A cross-sectional survey was conducted involving 52 elementary PE teachers (37 males, 15 females) from Yogyakarta, Indonesia. Physical literacy was assessed using a 20-item questionnaire designed to measure all five domains, with descriptive data presented as a percentage of total attainment compared with previously determined category thresholds. Teachers were found to be most competent in object control (55%) and cognitive understanding (53%), with moderate levels in environmental participation (51%), whereas motor competence (42%) and balance ability (39%) were comparatively low, with balance the weakest of the five domains. The integrated level of physical literacy of the teachers was 49% (average category). This gap between teachers' cognitive understanding and their physical and balance skills is likely to affect learning strategies in rhythmic activities, where balance and movement coordination are central topics. These findings support physical education courses focusing on motor and balance skills, rather than relying only on general awareness and promotion of physical literacy, in the professional development context of rhythmic activity teaching.